A chemical thin copper deposition process
By adopting the steps of oil removal, homogenization, chemical copper deposition and microcorrosion in the chemical thinning copper process of the circuit board, the problem of insufficient uniformity and adhesion of the copper layer is solved, and the yield rate of the finished circuit board is significantly improved.
Patent Information
- Application Number
- CN202411403292.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-10-09
AI Technical Summary
现有化学沉薄铜工艺中,铜层的均匀性和附着性较低,导致电路板成品的良品率较低。
A chemical thin copper process is adopted, including oil removal treatment, homogenization treatment, chemical copper depositing treatment and micro-corrosion treatment. By using a homogenizing agent to improve the wetting and adsorption properties of the circuit board substrate, the bond stability of the subsequent chemical precipitation copper liquid and the circuit board substrate is formed to form a copper layer with uniform and good adhesion.
It improves the uniformity and adhesion of the copper layer of the circuit board, improves the yield rate of the finished circuit board products, and is suitable for flexible printed circuit boards and integrated circuit packaging.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the field of circuit board processing, and more specifically, to a composite lithium adsorbent and a preparation process thereof. Background Art
[0002] A circuit board, also known as a PCB board, is a plate-shaped electronic device manufactured based on printing technology. Its main function is to transmit signals between various electronic devices, and is responsible for completing the connection between electronic components and realizing the transmission function of the entire circuit.
[0003] The manufacturing process of circuit boards generally includes drilling, grinding and deburring, board mounting, bulking and softening, water washing, drilling dirt removal, water washing, neutralization, oil removal, corrosion roughening, palladium activation, reduction, chemical copper deposition, water washing, board mounting, board electrification, drying and pattern transfer. The chemical copper deposition process is to deposit pure copper on the circuit board substrate through chemical reaction to form a fine copper layer circuit, thereby improving the conductivity and reliability of the circuit board.
[0004] The chemical copper deposition process includes chemical thin copper deposition and chemical thick copper deposition. Compared with chemical thick copper deposition, chemical thin copper deposition has a smaller thickness, lighter weight, better flexibility and plasticity, and can be easily bent into any shape. It is suitable for integrated and lightweight flexible printed circuit boards (FPCs), integrated circuit (IC) packaging, etc.
[0005] The current chemical copper deposition process generally involves first cleaning the circuit board substrate and then immersing it in a chemical copper deposition solution. The chemical copper deposition solution generally includes copper salts, reducing agents, chelating agents, etc. After immersion, a circuit board substrate with a copper layer is obtained. However, due to the thin thickness of the copper layer, problems such as unevenness and low adhesion are prone to occur during the deposition process, reducing the yield rate of the finished circuit board product. Summary of the invention
[0006] In order to solve the problem of low uniformity and adhesion of the copper layer of chemical copper deposition in the circuit board manufacturing process, the present application provides a chemical copper deposition process.
[0007] A chemical copper deposition process adopts the following technical solution:
[0008] A chemical copper deposition process comprises the following steps:
[0009] S1. Cleaning the circuit board substrate with a degreasing agent;
[0010] S2, homogenizing the circuit board substrate using a homogenizing agent to obtain a homogenized circuit board substrate;
[0011] S3, treating the homogenized circuit board substrate obtained in step S2 with a chemical copper deposition solution to obtain a copper deposition circuit board substrate; S4, performing micro-corrosion treatment on the copper deposition circuit board substrate to obtain a copper deposition circuit board.
[0012] By adopting the above technical scheme, the chemical copper deposition process of the present application first uses a degreasing agent to clean the circuit board substrate to remove dust and dirt generated in the previous process; then uses a leveling agent to perform a leveling treatment, so that the surface of the circuit board substrate has good wettability and adsorption, and improves the subsequent combination stability of the chemical copper deposition liquid and the circuit board substrate; then uses a chemical copper deposition liquid to perform a copper deposition treatment on the homogenized circuit board substrate, so that a uniform and well-adhesive copper layer is formed on the surface of the homogenized circuit board substrate, and a copper deposition circuit board substrate is obtained; then the copper deposition circuit board substrate is micro-etched, so that a uniform micro-etched surface is formed on the surface of the copper layer, and the copper layer of the circuit board obtained by this chemical copper deposition process has a thin thickness, good uniformity and adhesion, and the yield rate of the obtained circuit board product is high.
[0013] Preferably, the homogenizing agent in step S2 is made of the following raw materials in weight percentage: 0.5-1% chitosan quaternary ammonium salt, 0.1-0.3% polyvinyl alcohol, 10-20% ethanol, 0.1-0.3% sodium polyaspartate and the balance water.
[0014] By adopting the above technical scheme, ethanol has good permeability and wettability, and is mixed with water to improve the wettability of the homogenizing agent to the circuit board substrate. Under the action of ethanol, chitosan quaternary ammonium salt and polyvinyl alcohol are compounded in a better dosage ratio, and a uniform film with good adsorption and adhesion stability can be formed on the surface of the circuit board substrate. Sodium polyaspartate is dispersed in chitosan quaternary ammonium salt and polyvinyl alcohol, and can produce a good synergistic effect with chitosan quaternary ammonium salt and polyvinyl alcohol, thereby improving the copper deposition uniformity and adhesion stability during the subsequent chemical copper deposition liquid copper deposition treatment.
[0015] The leveling agent of the present application can be used to treat circuit board substrates of different materials, such as plastic substrates, ceramic substrates or glass fiber substrates, etc.
[0016] Preferably, the homogenization treatment in step S2 is performed at a temperature of 40-50° C. and for a time of 3-8 min.
[0017] By adopting the above technical solution, the optimal homogenization treatment time and temperature can enable the homogenization agent to form a uniformly dispersed film on the circuit board substrate, thereby increasing the contact area between the subsequent chemical copper plating solution and the circuit board substrate, thereby improving the uniformity and adhesion stability of copper plating.
[0018] Preferably, the chemical copper deposition solution in step S3 is composed of the following components in mass concentration:
[0019] Copper sulfate pentahydrate 5.9-9.8g / L
[0020] Sodium hydroxide 8-12g / L
[0021] Formaldehyde 3-6g / L
[0022] Complexing agent 1-3g / L
[0023] Stabilizer 2-5g / L.
[0024] By adopting the above technical scheme, copper sulfate pentahydrate provides copper ions, sodium hydroxide provides alkaline conditions, the complexing agent plays a role in complexing copper ions to prevent the copper ions from forming copper hydroxide precipitation under alkaline conditions, formaldehyde has a strong reducing property under the alkaline conditions of sodium hydroxide, and can reduce the copper ions complexed by the complexing agent into copper and then deposit them on the surface of the circuit board substrate, and the stabilizer plays a role in improving the copper deposition rate, thereby further improving the uniformity of copper deposition.
[0025] Preferably, the stabilizer is composed of ammonium persulfate and sodium N-hydroxymethylglycinate in a weight ratio of 1:(1-2).
[0026] By adopting the above technical scheme, using ammonium persulfate and sodium N-hydroxymethylglycinate in an optimal dosage ratio as stabilizers, the copper deposition rate of copper ions can be stably adjusted, thereby improving the adhesion uniformity and adhesion stability of the copper deposition while increasing the copper deposition rate.
[0027] Preferably, the complexing agent is composed of disodium ethylenediaminetetraacetate and sodium diethylenetriaminepenta(methylenephosphonate) in a weight ratio of 1:(0.3-0.5).
[0028] By adopting the above technical solution, the above complexing agent has a good synergistic effect, has a good complexing property for copper ions, can improve the dispersion uniformity of copper ions in the chemical copper precipitation solution, and makes it difficult for copper ions to form copper hydroxide precipitation.
[0029] Preferably, the processing time of step S3 is 10-15 minutes and the processing temperature is 28-35°C.
[0030] By adopting the above technical solution, the optimal processing temperature and time can improve the stability of copper deposition and form a uniform and stably adhered copper layer on the surface of the circuit board substrate.
[0031] Preferably, the copper-plated circuit board substrate obtained in step S3 has a copper-plated thickness of 10-20 microinches.
[0032] By adopting the above technical solution, the thickness of the copper deposition is controlled to 10-20 microinches, so that the copper layer has uniformity and adhesion stability while having good flexibility, which is suitable for integrated and lightweight flexible printed circuit boards and integrated circuits.
[0033] Preferably, in the step S4, a 3-8 g / L organic acid aqueous solution is used to micro-etch the copper-plated circuit board substrate, and the organic acid is any one of acetic acid, citric acid, glycolic acid, malic acid, and tartaric acid.
[0034] By adopting the above technical solution, the copper-plated circuit board substrate is micro-etched using the above-mentioned organic acid aqueous solution with a relatively optimal concentration, so that uniform micro-etching holes are formed on the surface of the copper-plated circuit board substrate, thereby improving the uniformity and stability of the copper layer.
[0035] Preferably, the temperature of micro-corrosion in step S4 is 20-35° C. and the time is 3-5 min.
[0036] By adopting the above technical solution, the better micro-corrosion conditions can make the surface of the copper-plated circuit board substrate corrode uniformly without affecting the thickness and uniformity of the copper layer.
[0037] In summary, this application has the following beneficial effects:
[0038] 1. The chemical copper deposition process of the present application first performs a degreasing treatment, and then uses a homogenizing agent to perform a homogenizing treatment on the circuit board substrate to improve the surface wettability and uniform adsorption of the circuit board substrate, and improve the contact area and copper deposition stability of the subsequent chemical copper deposition liquid and the circuit board substrate. The circuit board substrate is then subjected to a copper deposition treatment using a chemical copper deposition liquid to form a uniform and well-adhesive copper deposition circuit board substrate. Finally, the copper deposition circuit board substrate is micro-etched to obtain a copper deposition circuit board with good processing stability, which can improve the yield rate of the obtained circuit board product and is suitable for integrated and lightweight flexible printed circuit boards (FPCs), integrated circuit (IC) packaging, etc.
[0039] 2. The circuit board substrate is homogenized by using a homogenizing agent composed of chitosan quaternary ammonium salt, polyvinyl alcohol, ethanol, sodium polyaspartate and residual water, so that the circuit board substrate has better wettability and adhesion stability, thereby improving the uniformity and adhesion stability of subsequent chemical copper deposition liquid for thin copper deposition.
[0040] 3. By using a chemical copper deposition solution composed of copper sulfate pentahydrate, sodium hydroxide, formaldehyde, a chelating agent and a stabilizer, wherein the stabilizer is composed of ammonium persulfate and sodium N-hydroxymethylglycinate, and the chelating agent is composed of disodium ethylenediaminetetraacetate and sodium diethylenetriaminepenta(methylenephosphonate), the chemical copper deposition solution prepared in this way has good copper deposition rate, copper deposition uniformity and adhesion stability. DETAILED DESCRIPTION
[0041] The present application is further described in detail below with reference to the embodiments.
[0042] The following are the sources and specifications of some raw materials of this application. The raw materials used in the preparation examples and embodiments of this application can be obtained from the market, including but not limited to the raw materials of the following models and manufacturers. Raw materials with equivalent performance can be used:
[0043] 1. Chitosan quaternary ammonium salt: Hydroxypropyltrimethylammonium chloride chitosan HACC, content 98%, grams;
[0044] 2. Polyvinyl alcohol: polyvinyl alcohol 2488, content 99%;
[0045] 3. Sodium polyaspartate: CAS No. 181828-06-8, content 40%;
[0046] 4. Ammonium persulfate: CAS No. 7727-54-0, content 98.5%
[0047] 5. Sodium N-hydroxymethylglycinate: CAS No. 70161-44-3, content 99%;
[0048] 6. Disodium EDTA: content greater than 99%;
[0049] 7. Sodium diethylenetriamine penta (methylene phosphonate): CAS No. 22042-96-2, content 45%.
[0050] Preparation example of homogenizing agent
[0051] Preparation Example 1
[0052] Preparation Example 1 discloses a homogenizing agent, which is prepared by the following steps:
[0053] 1 kg of ethanol was added to 8.89 kg of water, and after stirring evenly, 0.05 kg of chitosan quaternary ammonium salt, 0.03 kg of polyvinyl alcohol and 0.03 kg of sodium polyaspartate were added, and stirred evenly to prepare a homogenizing treatment agent.
[0054] Preparation Example 2-3
[0055] The difference between Preparation Example 2-3 and Preparation Example 1 is that the amounts of raw materials used are different, see Table 1 below for details.
[0056] Table 1 Raw material dosage table of preparation examples 1-3
[0057]
[0058] Preparation Example 4
[0059] The difference between Preparation Example 4 and Preparation Example 1 is that an equal amount of chitosan quaternary ammonium salt is replaced by polyvinyl alcohol, and the rest is the same as Preparation Example 1.
[0060] Preparation Example 5
[0061] The difference between Preparation Example 5 and Preparation Example 1 is that an equal amount of polyvinyl alcohol is replaced by hydroxymethyl cellulose, and the rest is the same as Preparation Example 1.
[0062] Preparation Example 6
[0063] The difference between Preparation Example 6 and Preparation Example 1 is that an equal amount of sodium polyaspartate is replaced by sodium citrate, and the rest is the same as Preparation Example 1.
[0064] Preparation Example 7
[0065] The difference between Preparation Example 7 and Preparation Example 1 is that an equal amount of chitosan quaternary ammonium salt is replaced by chitosan, and the rest is the same as Preparation Example 1.
[0066] Preparation example of chemical copper plating solution
[0067] Preparation Example 8
[0068] Preparation Example 8 discloses a chemical copper deposition solution, which is composed of the following raw materials in mass concentration:
[0069] 20L tank liquid distribution tank, the tank body is made of PVC material:
[0070] First add 11602ml of water to the tank, then weigh 118g of copper sulfate pentahydrate, 160g of sodium hydroxide, 20g of disodium ethylenediaminetetraacetate as a complexing agent, and 40g of ammonium persulfate as a stabilizer, mix well, add 60g of formaldehyde, and add 8000ml of water to prepare a chemical copper precipitation solution.
[0071] Preparation Examples 9-10
[0072] The difference between Preparation Example 9-10 and Preparation Example 8 is that the amounts of raw materials used are different, see Table 2 below for details.
[0073] Table 2 Raw material dosage table of preparation examples 8-10
[0074]
[0075]
[0076] Preparation Example 11
[0077] The difference between Preparation Example 11 and Preparation Example 8 is that the type of complexing agent is different. The complexing agent is composed of disodium ethylenediaminetetraacetate and sodium diethylenetriaminepenta(methylenephosphonate). The amount of disodium ethylenediaminetetraacetate used is 15.39 g, and the amount of sodium diethylenetriaminepenta(methylenephosphonate) used is 4.62 g. The rest is the same as Preparation Example 8.
[0078] Preparation Example 12
[0079] The difference between Preparation Example 12 and Preparation Example 11 is that the amount of disodium ethylenediaminetetraacetate used is 13.33 g, the amount of sodium diethylenetriamine penta (methylenephosphonate) used is 6.67 g, and the rest is the same as Preparation Example 11.
[0080] Preparation Example 13
[0081] The difference between Preparation Example 13 and Preparation Example 12 is that the stabilizer is different. The stabilizer in Preparation Example 13 consists of ammonium persulfate and sodium N-hydroxymethylglycinate. The amount of ammonium persulfate is 20 g, and the amount of sodium N-hydroxymethylglycinate is 20 g. The rest is the same as Preparation Example 12.
[0082] Preparation Example 14
[0083] The difference between Preparation Example 14 and Preparation Example 13 is that the amount of ammonium persulfate used is 13.33 g, the amount of sodium N-hydroxymethylglycinate used is 26.67 g, and the rest is the same as Preparation Example 13.
[0084] Preparation Example 15
[0085] The difference between Preparation Example 15 and Preparation Example 13 is that in the stabilizer, the amount of ammonium persulfate used is 5 g, the amount of sodium N-hydroxymethylglycinate used is 5 g, the reduced weight of the stabilizer is made up with water, and the rest is the same as Preparation Example 13.
[0086] Example
[0087] Example 1
[0088] Embodiment 1 discloses a chemical copper deposition process, comprising the following steps:
[0089] S1. Use a 0.5mm polyimide film as the circuit board substrate and use a degreasing agent to clean it. The degreasing temperature is 50°C and the degreasing time is 3 minutes. After degreasing, rinse with water;
[0090] S2, soaking the circuit board substrate in a homogenizing agent at a temperature of 40° C. for 8 minutes to obtain a homogenized circuit board substrate;
[0091] S3, treating the homogenized circuit board substrate obtained in step S2 with the chemical copper plating solution obtained in Preparation Example 1, with the treatment time being 10 minutes and the treatment temperature being 28° C., to obtain a copper plating circuit board substrate;
[0092] S4, micro-etching the copper-plated circuit board substrate to obtain a copper-plated circuit board, in step S4, 3g / L citric acid aqueous solution is used as an organic acid aqueous solution to micro-etch the copper-plated circuit board substrate, the micro-etching temperature is 20°C, and the time is 5min;
[0093] The degreasing agent in step S1 is a commercially available weak acid or weak alkaline degreasing agent, and the model is not limited; the homogenizing agent in step S2 is a commercially available homogenizing agent, and the commercially available homogenizing agent is made of the following raw materials in weight percentage: 0.5% hydroxymethyl cellulose, 8% polyethylene glycol 800, 2% fatty alcohol polyoxyethylene ether and 89.5% water.
[0094] Example 2-3
[0095] The difference between Example 2-3 and Example 1 is that the sources of the chemical copper plating solution are different, and the preparation process parameters are also different, see Table 3 below for details.
[0096] Table 3 Parameters of Examples 1-3
[0097]
[0098] Embodiment 4-8
[0099] The difference between Examples 4-8 and Example 1 is that the sources of the chemical copper plating solution are different, see Table 4 below for details.
[0100] Table 4 Sources of the chemical copper plating solutions of Examples 4-8
[0101]
[0102]
[0103] Examples 9-15
[0104] The difference between Examples 9-15 and Example 7 is that the sources of the leveling agent are different, see Table 5 below for details.
[0105] Table 5 Sources of the homogenizing agents of Examples 9-15
[0106] Example Source of homogenizing agent Example 9 Preparation Example 1 Example 10 Preparation Example 2 Embodiment 11 Preparation Example 3 Example 12 Preparation Example 4 Example 13 Preparation Example 5 Embodiment 14 Preparation Example 6 Embodiment 15 Preparation Example 7
[0107] Comparative Example
[0108] Comparative Example 1
[0109] The difference between Comparative Example 1 and Example 1 is that the chemical thin copper deposition process is prepared by the following steps:
[0110] S1. Use a 0.5mm polyimide film as the circuit board substrate and use a degreasing agent to clean it. The degreasing temperature is 50°C and the degreasing time is 3 minutes. After degreasing, rinse with water;
[0111] S2, treating the circuit board substrate with the chemical copper plating solution prepared in Preparation Example 1, with the treatment time being 10 min and the treatment temperature being 28° C., to obtain a copper plating circuit board substrate;
[0112] S3, micro-etching the copper-plated circuit board substrate to obtain a copper-plated circuit board. In step S3, 3g / L citric acid aqueous solution is used as an organic acid aqueous solution to micro-etch the copper-plated circuit board substrate. The micro-etching temperature is 20°C and the time is 5 minutes.
[0113] Performance testing
[0114] The following is a performance test of the copper-plated circuit boards produced by the chemical copper-plated thin copper process of Examples 1-15 and Comparative Example 1:
[0115] 1. Copper deposition thickness test:
[0116] Use a thickness tester to test the copper thickness (unit: microinch), test 3 times, take the average value, test and record the test results.
[0117] 2. Adhesion test:
[0118] Use the hundred-grid test method to test the adhesion of the copper layer of the copper-immersion circuit board, test and record the test results;
[0119] 3. Backlight level test:
[0120] Use a backlight tester to test the backlight level of the copper-immersed circuit board. The higher the backlight level, the better the uniformity of the copper layer. Test and record the test results.
[0121] The following are the performance test data of the copper-plated circuit boards prepared in Examples 1-15 and Comparative Example 1, see Table 6 below for details.
[0122] Table 6 Performance data of copper-plated circuit boards prepared in Examples 1-15 and Comparative Example 1
[0123]
[0124] Combining Examples 1-3 and Examples 4-8 and Table 6, it can be concluded that the chemical copper plating solution prepared by compounding the complexing agent and the stabilizer in the preferred dosage ratio of the present application is applied to the chemical thin copper plating process of the present application, which can improve the uniformity and adhesion stability of the copper layer of the prepared copper plating circuit board. Compared with Examples 1-3, the copper layer thickness in Examples 6-7 reaches 12.2 microinches, the adhesion is increased from 3B to 4B, and the backlight level is also increased from 8 to 9. In Example 8, the amount of stabilizer is reduced, which reduces the synergistic effect of the complexing agent and the stabilizer. The thickness of the copper layer reaches 11.3 microinches, and the adhesion and uniformity of the copper layer are also significantly reduced. The adhesion can only reach 3B, and the backlight level can only reach 8.
[0125] Combining Example 7 and Example 9-15 and Table 6, it can be seen that the use of the homogenizing agent prepared in the application to homogenize the circuit board substrate and then perform copper deposition treatment can further improve the copper deposition uniformity and adhesion stability of the copper deposition circuit board. Compared with Examples 12-15, Examples 9-11 can achieve a copper deposition thickness of 15.4 microinches, an adhesion level of 5B, and a backlight level of 10, while Examples 12-15 do not use a better amount of chitosan quaternary ammonium salt, polyvinyl alcohol, sodium polyaspartate, ethanol and water for compounding, and the copper deposition thickness of the copper deposition circuit board obtained is reduced, and the backlight level is also reduced.
[0126] It can be seen from Examples 1-3 and Comparative Example 1 and Table 6 that the chemical thin copper deposition process of the present application can improve the copper deposition uniformity and adhesion stability of the copper deposition circuit board by combining the homogenization treatment with the copper deposition treatment process.
[0127] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A chemical thin copper deposition process, characterized in that: The following steps are involved: S1. Cleaning the circuit board substrate with a degreasing agent; S2, homogenizing the circuit board substrate using a homogenizing agent to obtain a homogenized circuit board substrate; S3, treating the homogenized circuit board substrate obtained in step S2 with a chemical copper deposition solution to obtain a copper deposition circuit board substrate; S4, performing micro-etching treatment on the copper-plated circuit board substrate to obtain a copper-plated circuit board; The homogenizing agent in step S2 is prepared from the following raw materials in weight percentage: 0.5-1% chitosan quaternary ammonium salt, 0.1-0.3% polyvinyl alcohol, 10-20% ethanol, 0.1-0.3% sodium polyaspartate and the balance water; The chemical copper plating solution in step S3 is composed of the following components in mass concentration: Copper sulfate pentahydrate 5.9-9.8g / L Sodium hydroxide 8-12 g / L Formaldehyde 3-6 g / L Complexing agent 1-3 g / L Stabilizer 2-5 g / L; The stabilizer is composed of ammonium persulfate and sodium N-hydroxymethylglycinate in a weight ratio of 1:(1-2); The complexing agent is composed of disodium ethylenediaminetetraacetate and sodium diethylenetriaminepenta(methylenephosphonate) in a weight ratio of 1:(0.3-0.5).
2. The chemical thin copper deposition process according to claim 1, characterized in that: The homogenization treatment in step S2 is performed at a temperature of 40-50° C. and for a time of 3-8 min.
3. The chemical thin copper deposition process according to claim 1, characterized in that: The processing time of step S3 is 10-15 minutes, and the processing temperature is 28-35°C.
4. The chemical thin copper deposition process according to claim 1, characterized in that: The copper deposition thickness of the copper deposition circuit board substrate prepared in step S3 is 10-20 micro inches.
5. The chemical thin copper deposition process according to claim 1, characterized in that: In the step S4, a 3-8 g / L organic acid aqueous solution is used to micro-etch the copper-plated circuit board substrate, and the organic acid is any one of acetic acid, citric acid, glycolic acid, malic acid, and tartaric acid.
6. The chemical thin copper deposition process according to claim 5, characterized in that: The temperature of micro-etching in step S4 is 20-35° C. and the time is 3-5 min.
Citation Information
Patent Citations
Electroless copper plating solution composition and preparation method thereof
CN101580953B
Manufacturing method for partial golden finger of circuit board
CN105228372A
Conducting planar material by plating film and its production
JP1997279352A